2015
DOI: 10.1517/14712598.2015.1064893
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the new infliximab biosimilar CT-P13 induction therapy in Crohn’s disease and ulcerative colitis – experiences from a single center

Abstract: This was the first study to prospectively evaluate the outcome of CT-P13 induction therapy in CD and UC. Our results confirm that induction with CT-P13 is safe and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 14 publications
3
49
0
2
Order By: Relevance
“…After the initial concerns about the extrapolation of clinical data from rheumatic indications to IBD, some paper has published on the efficacy and safety of CT-P13 in IBD patients. The increasing data on the comparable efficacy and safety profile may further decrease the fear of using biosimilar IFX routinely [3,[12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the initial concerns about the extrapolation of clinical data from rheumatic indications to IBD, some paper has published on the efficacy and safety of CT-P13 in IBD patients. The increasing data on the comparable efficacy and safety profile may further decrease the fear of using biosimilar IFX routinely [3,[12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…However, considering the number of full articles published in this topic, experience with the biosimilar IFX, mainly with long-term use, is still limited. We have already published an 8-week data of the efficacy of CT-P13 IFX biosimilar in Crohn's disease (CD) and ulcerative colitis (UC), and the multicenter Hungarian study has also confirmed the effectiveness and safety of CT-P13 therapy in the induction of clinical response and remission on large number of IBD patients very soon afterwards [3,4]. The ACCENT and ACT trials were the landmark randomized controlled trials demonstrating clearly that the originator IFX can maintain remission after inducing response in both diseases [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…After some case series, a large, prospective Hungarian multicenter study has confirmed the efficacy of CT-P13, the first infliximab biosimilar, in inducing and maintaining remission in both Crohn's disease (CD) and ulcerative colitis (UC) [1][2][3][4][5]. However, besides efficacy data, safety assessment is also very important when extrapolating indications for biosimilars.…”
Section: Introductionmentioning
confidence: 99%
“…10 Similarly, Kang et al reported 1 UC patient experiencing arthralgia and requiring discontinuation of CT-P13. 11 In the study by Keil et al, however, a total of 4 complications were identified during the CT-P13 therapy course, represented by pneumonia in 1 patient, herpes labialis in 1 patient, venous thrombosis in 1 patient and allergic reaction in 1 patient.…”
Section: Safetymentioning
confidence: 96%